2011
DOI: 10.1111/j.1447-0756.2011.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and pre‐pregnancy overweight: Possible factors involved in newborn macrosomia

Abstract: Abstractj og_1681 208..214Aim: Good glycemic control in gestational diabetes mellitus (GDM) seems not to be enough to prevent macrosomia (large-for-gestational-age newborns). In GDM pregnancies we studied the effects of glycemic control (as glycosylated hemoglobin [HbA1c]), pre-pregnancy body mass index (PP-BMI) and gestational weight gain per week (GWG-W) on the frequency of macrosomia. Methods: We studied 251 GDM pregnancies, divided into two groups: PP-BMI < 25.0 kg/m 2 (the nonoverweight group; n = 125), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
2
30
0
4
Order By: Relevance
“…In a systematic review, the association between gestational weight gain and birth weight was observed despite the use of different standard references and various methods of characterizing gestational weight gain (total, rate, or by trimester) [14]. This was consistent with the results among GDM pregnant women in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a systematic review, the association between gestational weight gain and birth weight was observed despite the use of different standard references and various methods of characterizing gestational weight gain (total, rate, or by trimester) [14]. This was consistent with the results among GDM pregnant women in this study.…”
Section: Discussionsupporting
confidence: 89%
“…However, there are still limited information on association between pre-pregnancy weight and birth weight among GDM women [13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Son yıllarda yapılan az sayıda çalışmada, gebelik öncesi BKİ'nin neonatal doğum ağırlığına etkisinin en az maternal hiperglisemi kadar önemli olduğu gösterilmiştir (10,11 Olmos ve ark. yaptığı çalışmada ise gebelik öncesi BKİ'nin 25 kg/m 2 ve üzerinde olmasının makrozomi ve iri bebek için maternal hiperglisemiden daha kuvvetli bir belirleyici olduğunu göstermiştir (12). Bu çalışmaya dahil edilen gebelerin de iyi glisemik kontrollü oldukları görüldü, ancak glisemik kontrol açısından üç grup arasında fark olmamasına rağmen iri bebek doğurma sıklığı fazla kilolu ve obez grupta literatür ile benzer şekilde daha fazlaydı.…”
Section: Discussionunclassified
“…Desde 1964, cuando la DMG emergió como subtipo de la diabetes mellitus (DM) 21 , la hipótesis de Pedersen fue aplicada a la DMG, de modo que el tratamiento de esta entidad ha consistido desde entonces en reducir los valores de glicemia materna, apuntando a un control glicémico óptimo, definido actualmente como glicemia en ayunas 70-90 mg/dl, pre-prandiales de 70-105 mg/dl, y 1 h postprandial 90-120 mg/dl [22][23][24] . Sin embargo, como veremos más adelante, parece ser insuficiente para evitar la macrosomia fetal.…”
Section: Fisiopatología Tradicional De La Macrosomía En Dmg: La Hipótunclassified
“…En un estudio publicado recientemente, demostramos que la tasa de recién nacidos GEG fue de 18%, en 251 embarazadas con DMG a pesar de un óptimo control glicémico 24 . Al clasificar las madres en dos grupos según su índice de masa corporal (IMC) pregestacional, las tasas de GEG fueron de 10% para el grupo sin sobrepeso y de 25% para las madres con sobrepeso pregestacional, a pesar que ambos grupos presentaban valores de glicemia media y de hemoglobina glicosilada similares al final del embarazo.…”
Section: Fisiopatología Tradicional De La Macrosomía En Dmg: La Hipótunclassified